Intelligence functions disorders in patients with complex partial epilepsy - Stella, Florindo [UNESP]; Maciel, Jayme Antunes (FapUNIFESP (SciELO), 2004)
Objective: To compare the performance of patients with complex partial epilepsy with the normal controls in the subtests of an instrument used to assess intelligence function. Method: Fifty epileptic patients, whose ages ranged from 19 to 49 years and 20 normal controls without any neuropsychiatric disorders. The Wechsler-Bellevue adult intelligence test was applied in groups, epileptic patients and control subjects. This test is composed of several subtests that assess specific cognitive functions. A statistical analysis was performed using non-parametric tests. Results: All the Wechsler-Bellevue subtests revealed that the intelligence functions of the patients were significantly inferior to that of the controls (p<0.05). This performance was supported by the patient's complaints in relation to their cognitive performance. Conclusion: Patients with complex partial epilepsy presented poorer results in the intelligence test when compared with individuals without neuropsychiatric disorders.
Keywords: Cognitive functions; Epilepsy; Intelligence; adult; clinical article; cognition; complex partial seizure; controlled study; female; human; intellectual impairment; intelligence; male; performance; Adult; Case-Control Studies; Cognition Disorders; Epilepsy, Complex Partial; Female; Humans; Male; Middle Aged; Statistics, Nonparametric; Wechsler Scales